Comparison of non-contact infrared skin thermometers. (17th February 2018) - Fletcher, Thomas; Whittam, Aaron; Simpson, Rob; Machin, Graham
Abstract: Non-contact infra-red skin thermometers (NCITs) are becoming more prevalent for use in medical diagnostics. Not only are they used as an alternative means of estimating core body temperature but also to assess the diabetic foot for signs of inflammation prior to ulceration. Previous investigations have compared the performance of NCITs in a clinical setting against other gold standard methods. However, there have been no previous investigations comparing the performance of NCITs in assessing temperature measurement capability traceable to the International Temperature Scale of 1990 (ITS-90). A metrological assessment of nine common NCITs was carried out over the temperature range of 15–45 °C using the National Physical Laboratory's blackbody reference sources to identify their accuracy, repeatability, size-of-source and distance effects. The results are concerning in that five of the NCITs fell far outside the accuracy range stated by their manufacturers as well as the medical standard to which the NCITs are supposed to adhere. Furthermore, a 6 °C step change in measurement error over the temperature range of interest for the diabetic foot was found for one NCIT. These results have implications for all clinicians using NCITs for temperature measurement and demonstrate the need for traceable calibration to ITS-90.